Politics and education: a case study of political participation of women in Iran - Shojaei, Seyedeh Nosrat; Ku Samsu, Ku Hasnita; Asayesh, Hossein (Marsland Press, 2011)
This article studies the structural obstacles of women’s political participation in Iran. The objective of the study has been achieved by answering the question; how structural factors (Education and knowledge) act as obstacles to women's participation in top political positions in Iran? A qualitative case study method is used in the paper and the primary data are collected mainly through in-depth interviews with five informants by using purposive technique. The analysis of the study is supported by resources theory. The findings of the article suggested that inadequate intellectual resources act as the structural obstacles of Iranian women in politics.